STRATEGI BRANDING ECO GREEN CAMPAIGN KOMUNITAS MAT PECI UNTUK MEWUJUDKAN WISATA ALAM DENGAN KEARIFAN LOKAL - Nada Arina Romli; Dini Safitri; Prima Yustitia Nurul Islami (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
The Ciliwung River is a source of life for the community around the watershed (Watershed)in the Jakarta, Bogor and Bekasi areas. But now there has been tremendous damage to theecosystem in Ciliwung and most of it is caused by human activities. Some of the damage to theCiliwung river ecosystem includes waste pollution due to industrial and household waste due toland conversion from upstream to downstream, forced taking of river border areas to be used ashousing, hotels, villas, factories and shopping centers and offices. The Mat Peci Community is acommunity that cares about the Ciliwung River which has the aim of providing education aboutthe importance of preserving the Ciliwung River to protect natural ecosystems.This study aims to examine in more depth (1) to find out the preparation stage in making theEco Green campaign Branding Strategy to realize nature tourism with local wisdom, (2) todetermine the stages of implementation and promotion increate a Branding Eco Green campaign Strategy to realize nature tourism with local wisdomand (3) to find out the evaluation stage in making an Eco Green campaign Branding Strategy torealize nature tourism with local wisdom. This study uses a qualitative research method with a casestudy research design. Data collection techniques use semi-structured interviews and passiveparticipant observation and literature review. The sampling technique uses a snowball samplingtechnique and the grand theory used is the theory of social construction of reality. This researchwas conducted at the Mat Peci Community, Srengseng, South Jakarta.The results of this study indicate that the community strategy carried out by the Mat Pecicommunity is in line with the explanation above, namely community development based on selfrelianceand participatory. There are three community development strategies that are carried out,namely environmental conservation (Environment), providing education about river conservation(Education), and independent empowerment of residents around the Ciliwung river basin(empowerment). Dialogic communication carried out by the Mat Peci community is acollaborative concept, namely building interactions between residents, the Mat Peci communityand also organizations, companies or other institutions by building facilities, infrastructure orcarrying out activities that provide knowledge and benefits both scientifically and economically soas to create 'capital'. social', namely the economic independence of citizens, where residents canuse infrastructure to meet their needs or make colors for river conservation and recycle waste as asource of livelihood.